Architectural acoustics illustrated - Ermann, Michael (Michael A.)
"Translates the quantitative and qualitative content of acoustics into the graphic language of architecture and outlines the best practices for limiting or mitigating noise in buildings"--Provided by publisher.
RC Songcayauon (Recommending faculty) AY 2022-2023
Includes bibliographical references and index.
Keywords: Architectural acoustics; Architectural acoustics -- Pictorial works; ARCHITECTURE / Methods & Materials; TECHNOLOGY & ENGINEERING / Acoustics & Sound